Let t=0 for 2013, t=1 for 2014, t=2 for 2015, t=3 for 2016, t=4 for 2017.

Assuming the exponential growth rate as,

\(y(t)=a xx ekt\) where y is the % of students having serious psychosocial distress at time ta is value at starting t=0k is the rate of growtht is time

Therefore, at t=4, y=17.1

Thus,

\(17.1=10.7*e^(k*4)\)

\(e^(4k)=log_e(17.1/10.7)=0.4688\)

k=0.1172

Hence, the equation of exponential growth rate is

\(y(t)10.7*e^(0.1172t)\)

Thus the annual growth rate is calculated at t=1 we get

\(y(1)=10.7*e^(0.1172*1)\)

\(y(1)=10.7*e^(0.1172)\)

y(1)=12.03

Hence, the annual growth rate in the percentage of students reporting serious psychosocial distress in the past month is 12.03%.

Assuming the exponential growth rate as,

\(y(t)=a xx ekt\) where y is the % of students having serious psychosocial distress at time ta is value at starting t=0k is the rate of growtht is time

Therefore, at t=4, y=17.1

Thus,

\(17.1=10.7*e^(k*4)\)

\(e^(4k)=log_e(17.1/10.7)=0.4688\)

k=0.1172

Hence, the equation of exponential growth rate is

\(y(t)10.7*e^(0.1172t)\)

Thus the annual growth rate is calculated at t=1 we get

\(y(1)=10.7*e^(0.1172*1)\)

\(y(1)=10.7*e^(0.1172)\)

y(1)=12.03

Hence, the annual growth rate in the percentage of students reporting serious psychosocial distress in the past month is 12.03%.